2019
DOI: 10.1021/acsomega.9b00509
|View full text |Cite
|
Sign up to set email alerts
|

Probing the Effect of Glucose on the Activity and Stability of β-Glucosidase: An All-Atom Molecular Dynamics Simulation Investigation

Abstract: β-Glucosidase (EC 3.2.1.21) plays an essential role in the removal of glycosyl residues from disaccharide cellobiose to produce glucose during the hydrolysis of lignocellulosic biomass. Although there exist a few β-glucosidase that are tolerant to large concentrations of glucose, these enzymes are typically prone to glucose inhibition. Understanding the basis of this inhibition is important for the production of cheaper biofuels from lignocellulose. In this study, all - atom molecular dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 45 publications
3
15
0
Order By: Relevance
“…To estimate the consequences for ligand accessibility, we have analyzed the average active site width as the mean distance between the Cα atoms of the active site loops ( R Av ) ( Figure 4(B,C) ). This measure has already proved to be well correlated with ligand accessibility/resistance in previous studies (Konar et al., 2019 ; Lima et al., 2020 ). First, we have measured the R av statistics for conformations with the potential of mean force (PMF) at the 20% more favorable values from our MetaDy analyses (i.e.…”
Section: Resultsmentioning
confidence: 66%
“…To estimate the consequences for ligand accessibility, we have analyzed the average active site width as the mean distance between the Cα atoms of the active site loops ( R Av ) ( Figure 4(B,C) ). This measure has already proved to be well correlated with ligand accessibility/resistance in previous studies (Konar et al., 2019 ; Lima et al., 2020 ). First, we have measured the R av statistics for conformations with the potential of mean force (PMF) at the 20% more favorable values from our MetaDy analyses (i.e.…”
Section: Resultsmentioning
confidence: 66%
“…A comparison with PDB structure 3F5K and 2O9P indicates the presence of the +2 subsite in B8CYA8 which can potentially assist in the non-productive binding of the substrate. Recently we showed that in the presence of low substrate concentrations (1 mM p NPGlc), B8CYA8 is inhibited at all concentrations of glucose [48]. We also reported by MD simulations of B8CYA8 in the presence of glucose that at the gatekeeper region, the number of glucose molecules increases significantly with glucose concentration than inside the pocket [48].…”
Section: Discussionmentioning
confidence: 96%
“…Recently we showed that in the presence of low substrate concentrations (1 mM p NPGlc), B8CYA8 is inhibited at all concentrations of glucose [48]. We also reported by MD simulations of B8CYA8 in the presence of glucose that at the gatekeeper region, the number of glucose molecules increases significantly with glucose concentration than inside the pocket [48]. Our results reported here do not preclude the possibility of substrate binding non-productively to the +1 to +2 subsite or the possibility of glucose binding at this subsite to relieve the non-productive binding of the substrate and increase enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, minimal topological modifications represent a promising strategy for suggesting mutations, especially in the beta-glucosidase loop regions that surround the active site. The topology and dynamics of these loops can allow or restrict movements involved in glucose entrance and exit (i.e., glucose tolerance) 30,32,36,43 or also can affect the thermostability [41][42][43] . These are both examples of industrially desirable characteristics for these and other proteins.…”
Section: Implications For Protein Engineeringmentioning
confidence: 99%